Analisis Pengaruh E-Wallet Terhadap Perilaku Menabung dan Pengeluaran Konsumen di Indonesia - Siti Afiyah Hardinar Nazhifah; Zakia Zamielna Putri; Shandy Zahra Permadi; Shakila Dian Nova; Alsheira Nasywa; Ahmad Setiawan Nuraya (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of e-wallet usage on consumer savings behavior and spending patterns in Indonesia. In the digital era, e-wallets have become a commonly used transaction tool due to their convenience, speed, and various promotional features offered. However, behind their convenience, e-wallets also pose new challenges in personal financial management, such as increased consumer behavior and decreased savings intentions. This study uses a quantitative explanatory approach with a cross-sectional survey design to understand the relationship between the intensity of e-wallet usage and consumer savings and spending habits. The results of the study show that ease of transactions and digital incentives can encourage spontaneous consumption behavior and weaken awareness of the importance of saving. However, with adequate digital financial literacy, e-wallets also have the potential to be a tool in managing finances wisely. This study emphasizes the importance of digital financial education so that people can utilize financial technology in a healthy and sustainable manner.